Does Blue Uniform Color Enhance Winning Probability in Judo Contests? - Dijkstra, Peter D.; Preenen, Paul T. Y.; van Essen, Hans (Frontiers in Psychology, 2018)
The color of an athlete's uniform may have an effect on psychological functioning and consequently bias the chances of winning contests in sport competition. Several studies reported a winning bias for judo athletes wearing a blue outfit relative to those wearing a white outfit. However, we argue there is no winning bias and that previous studies were confounded and based on small and specific data sets. We tested whether blue biases winning in judo using a very extensive judo data set (45,874 contests from all international judo tournaments between 2008 and 2014). In judo, the first called athlete for the fight used to wear the blue judogi but this was changed to the white judogi in 2011. This switch enabled us to compare the win bias before and after this change to isolate the effect of the color of the judogi. We found a significant win bias for the first called athlete, but this effect was not significantly related to the color of the judogi. The lack of a significant win effect of judogi color suggests that blue does not bias winning in judo, and that the blue-white pairing ensures an equal level of play. Our study shows the importance of thoroughly considering alternative explanations and using extensive datasets in color research in sports and psychology.